2021
DOI: 10.1016/j.celrep.2021.108951
|View full text |Cite
|
Sign up to set email alerts
|

Activity-dependent somatodendritic dopamine release in the substantia nigra autoinhibits the releasing neuron

Abstract: Highlights d Somatodendritic DA release is decreased by single-cell Na +channel inhibition d Intracellular BoNT/A LC cleaves SNAP-25 and eliminates DA release from the cell d Synaptic GABA input to SNc DA neurons is unaffected by intracellular BoNT/A LC d Somatodendritic DA in the SNc autoinhibits the neuron that releases it

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 89 publications
2
29
0
Order By: Relevance
“…Whole-cell dialysis 10 mM EGTA fully disinhibited the cocaine-mediated reduction of the firing rate of LC neurons (Figures 4A and 4B), suggesting that local NE release from the recorded LC neuron is sufficient to inhibit its firing activity. This observation is consistent with a recent study revealing that local DA release cell autonomously regulates their activity in substantia nigra pars compacta (SNc) (Hikima et al, 2021). Interestingly, previous studies reported that cocaine-induced hyperpolarization exists in the presence of calcium chelators in the internal solution (Courtney and Ford, 2014;Courtney et al, 2012;Ford et al, 2009); this discrepancy might be due to different experimental conditions such as species (rat versus mouse), animal age (postnatal 8-10 days versus 3-6 weeks), temperature (room temperature versus physiological temperature), and cell types (DA neurons versus LC-NE neurons).…”
Section: Discussionsupporting
confidence: 93%
“…Whole-cell dialysis 10 mM EGTA fully disinhibited the cocaine-mediated reduction of the firing rate of LC neurons (Figures 4A and 4B), suggesting that local NE release from the recorded LC neuron is sufficient to inhibit its firing activity. This observation is consistent with a recent study revealing that local DA release cell autonomously regulates their activity in substantia nigra pars compacta (SNc) (Hikima et al, 2021). Interestingly, previous studies reported that cocaine-induced hyperpolarization exists in the presence of calcium chelators in the internal solution (Courtney and Ford, 2014;Courtney et al, 2012;Ford et al, 2009); this discrepancy might be due to different experimental conditions such as species (rat versus mouse), animal age (postnatal 8-10 days versus 3-6 weeks), temperature (room temperature versus physiological temperature), and cell types (DA neurons versus LC-NE neurons).…”
Section: Discussionsupporting
confidence: 93%
“…The dendrites of dopamine neurons perform roles traditionally associated with axons, reliably backpropagating action potentials (Hage and Khaliq, 2015; Hausser et al, 1995) and releasing dopamine (Beckstead et al, 2004; Gantz et al, 2013; Gantz et al, 2018; Hikima et al, 2021; Lebowitz et al, 2021). In this study we reveal properties of DA axons that are reminiscent of dendritic functions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, dopamine-releasing neurons are unlikely to cause excitotoxicity in medium spiny neurons [ 36 , 37 ]. In addition, nigrostriatal dopaminergic neurons themselves express D2R, and the released dopamine is thought to exert autocrine inhibitory effects on the excitability of these neurons [ 38 , 39 , 40 ]. Dopaminergic neurons perform the tonic release of dopamine according to the pacemaking activity and switch to phasic release when necessary; the released dopamine may exert negative feedback on dopaminergic neurons.…”
Section: Dopaminergic Neurons and Astrocytesmentioning
confidence: 99%